Faktor-Faktor Penahanan Dana (Cash Holding) - Chistian, Natalis; Fauziah, Fera (Global Financial Accounting Journal, 2017)
This research tests the effect to examine factors that effect of cash holding in Indonesian stock exchange. Independent variable used in ths study is firm size, market to book ratio, leverage, net working capital, cash flow, ROA, investment in fixed asset, dividends, and board size. This research uses non-financial firm in Indonesian Stock Exchange period 2010-2014. Sample of this research consist of 218 non-financial company from 508 company listed in Indonesian Stock Exchange. The sampling uses purposive sampling. Hypothesis test is multiple linear regression uses eviews. The results showed that the market-to-book ratios, cash flow, dividends and board size positively significant effect on corporate cash holding, firm size and ROA significant negative effect on corporate cash holding, net working capital, leverage, and investment in fixed assets insignificant on corporate cash holding.